Perception of residents in the state of Selangor on affordable housing price with the expected criteria - Mohamed Osman, Mariana; Rabe, Noor Suzilawati; Zainudin, Farah Eleena (American Scientific Publishers, 2018)
The development of affordable housing in Malaysia has become a necessity due to the level of income people are low according to the national household income survey 2012 and 2014. This study attempts to use qualitative research methodology to access the level of satisfaction towards the criteria for affordable housing distribution in Selangor. In fact, the research objective for this study are to identify the most importance criteria in the provision of affordable house. Next, to analyses the affordable house price expected by the residents and lastly to examined the relation of affordable housing criteria with the household income and number of household